NUMERICAL METHODS FOR SOLVING THE FIRST ORDER LINEARFREDHOLM-VOLTERRA INTEGRO-DIFFERENTIAL EQUATIONS - Omran, H H (Al-Nahrain Journal of Science, 2018)
The aim of this work is to present numerical methods for solving the first order linear Fredholm-Volterra integro-differential equations of the second kind. These methods namely are the repeated Trapezoidal method and the repeated Simpson's 1/3 method. These techniques transform the integro-differential equations to a system of algebraic equations. Some numerical examples are presented to illustrate the efficiency and accuracy of these methods.